2014
DOI: 10.1002/jmri.24661
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast-enhanced MRI of the prostate with high spatiotemporal resolution using compressed sensing, parallel imaging, and continuous golden-angle radial sampling: Preliminary experience

Abstract: Purpose To demonstrate dynamic contrast-enhanced (DCE) magnetic resonance imaging (MRI) of the prostate with both high spatial and temporal resolution via a combination of golden-angle radial k-space sampling, compressed sensing, and parallel-imaging reconstruction (GRASP), and to compare image quality and lesion depiction between GRASP and conventional DCE in prostate cancer patients. Materials and Methods Twenty prostate cancer patients underwent two 3T prostate MRI examinations on separate dates, one usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
83
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 46 publications
(37 reference statements)
2
83
0
Order By: Relevance
“…1,2,18,21,22,25,28,29 All of these studies found that the combined methodology produced images deemed acceptable or not significantly different from fully sampled images, while employing acceleration rates from 23 to 7.23, depending on the application. Five of these studies compared the combined method with the standard imaging protocol for the respective study's imaging application.…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…1,2,18,21,22,25,28,29 All of these studies found that the combined methodology produced images deemed acceptable or not significantly different from fully sampled images, while employing acceleration rates from 23 to 7.23, depending on the application. Five of these studies compared the combined method with the standard imaging protocol for the respective study's imaging application.…”
Section: Methodsmentioning
confidence: 98%
“…32 A total of 275 subjects were imaged across the 18 studies (range, 3-34; mean 5 15.28; median 5 11.5; standard deviation 5 10.23). 7 studies imaged healthy subjects, 15,[19][20][21]23,24,27 and 11 imaged patients referred for the type of imaging under consideration 1,2,14,[16][17][18]22,25,26,28,29 ( Figure 5). …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compressed sensing techniques have been implemented into DCE sequences to improve spatiotemporal resolution or increase the coverage. Recently, Rosenkrantz et al reported the use of a highspatiotemporal resolution DCE technique GRASP (Golden-angle Radial Sparse Parallel), which allows for image acquisition with spatial resolution of 1.1 9 1.1 9 3.0 mm and temporal resolution of 2.3 s [102].…”
Section: Dynamic Contrast-enhanced Imagingmentioning
confidence: 99%